2013
DOI: 10.1089/neu.2012.2339
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Alterations in Human Traumatic Brain Injury: Changes in Mitochondrial Morphology Reflect Regional Levels of Injury Severity

Abstract: Mitochondrial dysfunction may be central to the pathophysiology of traumatic brain injury (TBI) and often can be recognized cytologically by changes in mitochondrial ultrastructure. This study is the first to broadly characterize and quantify mitochondrial morphologic alterations in surgically resected human TBI tissues from three contiguous cortical injury zones. These zones were designated as injury center (Near), periphery (Far), and Penumbra. Tissues from 22 patients with TBI with varying degrees of damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 58 publications
5
30
0
Order By: Relevance
“…Axonal shear stretch leads to the opening of voltage-gated calcium channels that, ultimately, precipitates mitochondrial dysfunction, bioenergetic failure, and the release of secondary messengers that end in apoptosis and death (Balan et al, 2013; Glenn et al, 2003; Lifshitz et al, 2003; Marcoux et al, 2008; Ragan et al, 2013; Xu et al, 2010). Thus, mitochondria play a central role in cerebral metabolism and regulation of oxidative stress, excitotoxicity, and apoptosis in acute brain injury; however, the mechanistic response and time course following diffuse TBI, especially in the immature brain at differing developmental stages, has limit investigation (Balan et al, 2013; Gilmer et al, 2010; Lifshitz et al, 2004; Robertson et al, 2009). Furthermore, the challenge of extrapolating adult models of diffuse TBI to pediatric models includes developmental differences in biomechanical properties and biological responses that vary in the infant, toddler, adolescent, and adult (Grate et al, 2003; Ibrahim et al, 2010; S.…”
Section: Introductionmentioning
confidence: 99%
“…Axonal shear stretch leads to the opening of voltage-gated calcium channels that, ultimately, precipitates mitochondrial dysfunction, bioenergetic failure, and the release of secondary messengers that end in apoptosis and death (Balan et al, 2013; Glenn et al, 2003; Lifshitz et al, 2003; Marcoux et al, 2008; Ragan et al, 2013; Xu et al, 2010). Thus, mitochondria play a central role in cerebral metabolism and regulation of oxidative stress, excitotoxicity, and apoptosis in acute brain injury; however, the mechanistic response and time course following diffuse TBI, especially in the immature brain at differing developmental stages, has limit investigation (Balan et al, 2013; Gilmer et al, 2010; Lifshitz et al, 2004; Robertson et al, 2009). Furthermore, the challenge of extrapolating adult models of diffuse TBI to pediatric models includes developmental differences in biomechanical properties and biological responses that vary in the infant, toddler, adolescent, and adult (Grate et al, 2003; Ibrahim et al, 2010; S.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature suggests that a main component of this secondary injury cascade is altered mitochondrial bioenergetics and cerebral metabolic crisis (Gilmer et al, 2009; Robertson et al, 2006). Mitochondria play a pivotal role in cerebral metabolism and regulation of oxidative stress, excitotoxicity, and apoptosis (Balan et al, 2013; Gilmer et al, 2009; Lifshitz et al, 2003; Robertson, 2004). Cerebral metabolic crisis displays regional heterogeneity, varies temporally post-injury and with gradation of injury severity, and is often sustained for a prolonged period of time (Lifshitz et al, 2003; Marcoux et al, 2008b; Ragan et al, 2013; Robertson et al, 2006, 2009; Saito et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction may be central to the pathophysiology of TBI through metabolic derangements, oxidative stress, and apoptosis. In fact, a recent study showed mitochondrial ultrastructural alterations at progressive distances from the center of the penumbra in tissue samples from TBI patients [81]. In the setting of TBI, the production of ROS is enhanced [82][83][84], and the neuroprotective systems become overwhelmed and result in oxidative cell damage.…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%